Rice fortification in Bangladesh: Technical feasibility and regulatory requirement for introducing rice fortification in public modern storage/distribution of fortified rice through PFDS channels - Andrade, Juan E.; Ali, Abu Noman Mohammad Atahar; Chowdhury, Reajul; Crost, Benjamin; Hoffmann, Vivian; Mustafa, Shoumi; Shaima, Nabila Afrin (International Food Policy Research Institute, 2021)
Micronutrients, often referred to as vitamins and minerals are vital to healthy development, disease prevention, and wellbeing. Although only required in small amounts, micronutrients are not produced in the body and must be derived from the diet. Commonly cited micronutrients include Iron, Vitamins A, B, D, Iodine, and Zinc. Malnutrition in micronutrients tends to trap populations in a vicious cycle of poverty, causing adults to be less productive and preventing children from reaching their full potential, and exacerbating household poverty in general. Addressing the problem of micronutrient malnutrition, therefore, provides substantial benefits to the cause of development (Ara et al. 2019). The fortification of staple food items including rice to deliver vital micronutrients offers a unique opportunity to target the vulnerable populace – mostly women, young children and female adolescents – at a low cost, and importantly, without forcing a change in dietary habits.2 Although considerable investments are currently being made to improve micronutrient nutrition outcomes around the world, such efforts generally take time to provide results.